2016
DOI: 10.1111/febs.13901
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone improves redox state in ataxia telangiectasia cells by promoting an NRF2‐mediated antioxidant response

Abstract: Ataxia telangiectasia (A-T) is a rare incurable neurodegenerative disease caused by biallelic mutations in the gene for ataxia-telangiectasia mutated (ATM). The lack of a functional ATM kinase leads to a pleiotropic phenotype, and oxidative stress is considered to have a crucial role in the complex physiopathology. Recently, steroids have been shown to reduce the neurological symptoms of the disease, although the molecular mechanism of this effect is largely unknown. In the present study, we have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 73 publications
(99 reference statements)
1
26
1
1
Order By: Relevance
“…Responding to ROS, NRF2 plays a vital role in transcriptionally regulating the expression of antioxidants genes including G6PD. 17 , 18 Immunoblotting analysis indicated that oxaliplatin treatment induced NFR2 activation and G6PD expression in CRC cells ( Figure 3b ). Also, RNAi depletion of NRF2 decreased G6PD mRNA and protein levels in these oxaliplatin-treated CRC cells ( Figures 3b and c ).…”
Section: Resultsmentioning
confidence: 99%
“…Responding to ROS, NRF2 plays a vital role in transcriptionally regulating the expression of antioxidants genes including G6PD. 17 , 18 Immunoblotting analysis indicated that oxaliplatin treatment induced NFR2 activation and G6PD expression in CRC cells ( Figure 3b ). Also, RNAi depletion of NRF2 decreased G6PD mRNA and protein levels in these oxaliplatin-treated CRC cells ( Figures 3b and c ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, zinc supplementation exerts a protective role against damage to the vascular system. The mechanisms by which zinc protects the blood vessels include the regulation of Nrf2, a transcription factor important for the expression of genes encoding antioxidant enzymes and for the induction and expression of metallothionein [32,33,34]. …”
Section: Biochemical Aspectsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] Li et al reported the role of ATM in balancing HDAC4 function in AT neurons. [21][22][23][24][25][26][27] Li et al reported the role of ATM in balancing HDAC4 function in AT neurons.…”
Section: Introductionmentioning
confidence: 99%